Gallium-68 Dota-Tate positron emission tomography/computed tomography: Scintigraphic changes of adrenal glands following management of ectopic cushing′s syndrome by steroidogenesis inhibitors - Yu-Ting Huang; Shaikh Aziz; Aravind Ravi Kumar (World Journal of Nuclear Medicine)
In the era of emerging functional imaging techniques, an understanding of the effects of hormonal therapies on the scintigraphic appearance of endocrine organs is desirable to minimize the erroneous scan interpretation. The mechanisms by which changes in the scintigraphic appearance of endocrine organs occur however sometimes remain ambiguous. This case demonstrates the gallium-68 (Ga-68) DOTA-TATE positron emission tomography/computed tomography (CT) appearance of adrenal glands following management with steroidogenesis inhibitors. The potential mechanisms underlying this change are discussed. A 17-year-old boy with adrenocorticotropic hormone (ACTH) dependent Cushing′s syndrome secondary to ectopic ACTH secretion underwent pre- and post-metyrapone and dexamethasone treatment Ga-68 DOTA-TATE scans 4 months apart. Pretreatment, both adrenals demonstrated normal symmetrical prominent Ga-68 DOTA-TATE uptake and normal CT appearance. The posttherapy scan revealed marked symmetrical suppression of Ga-68 DOTA-TATE uptake, but with bilateral adrenal hypertrophy on CT.